Gambaran Efikasi Diri Karier Pada Siswa SMK - Dina Rahmadina; Nurfarhanah; Rahmi Dwi Febriani; Nilma Zola (Journal of Society Counseling, 2026)
This study aimed to describe the career self-efficacy of tenth-grade students at SMK Negeri 9 Padang. Career self-efficacy refers to students’ beliefs in their ability to understand themselves, explore career opportunities, make career decisions, develop plans, and solve problems related to their future careers. The study employed a descriptive quantitative design involving 462 students from the Culinary and Hospitality programs as the population. A sample of 214 students was selected through simple random sampling using Slovin’s formula with a 5% margin of error. Data were collected using a career self-efficacy scale consisting of five dimensions: self-appraisal, gathering occupational information, goal selection, planning, and problem solving. The instrument was tested for validity and reliability, resulting in 22 valid items. The data were analyzed using descriptive statistical techniques and percentages. The results showed that overall career self-efficacy was predominantly in the high category, with 62% of students demonstrating strong confidence in managing career-related tasks. Similar findings were observed across all dimensions, namely self-appraisal (47%), gathering occupational information (44%), goal selection (52%), planning (47%), and problem solving (52%). These results indicate that most students possess a high level of confidence in their career development and decision-making processes.